The Analysis of the Grade 10 Students’ Retention Level of Basic Biology Concepts and Terminologies in Relation to their Learning Styles - James Ollero (Universitas Islam Indonesia, 2023)
Science subjects, or specifically biology, contain many concepts and terminologies that require extensive effort in memorizing. As a result, students are employing their own learning styles to learn things in the best possible way. Thus, this study aimed to investigate the possible relationship between the students’ retention level in biology and learning styles in the course. A descriptive-correlational research design was utilized to determine the relationship between the retention level and learning styles of Grade 10 students in biology. A retention test was conducted that seeks to evaluate the retention level of the respondents in their biology subjects. Respondents were asked to select the best way on how they are learning biology effectively, as part of the retention test. Each of the ways indicated corresponds to a specific learning style category following the Visual, Auditory, Read, and Kinesthetic (VARK) Learning styles Model. Findings revealed that the majority of the respondents were Visual Learners comprised of 51.61% of the population and a portion of 38.71% of the respondents have an Outstanding Level of Retention in basic biology concepts and terminologies. In addition, the overall retention level category of the population is with Satisfactory Level of Retention, which was based on their mean percentage score. Furthermore, it has been proven that there is none to very weak relationship between the retention level and learning styles of the respondents where it gained a correlation level of 0.151, on which correlation is significant at 0.01 level, which strength of the linear relationship is categorized under none to the extremely weak relationship. It has been concluded that many factors, aside from learning styles, may affect the students’ retention of learning biology.